More than ever, scientists need to engage with the public: the stakes are high and they may be for keeps - Smith, David Roy (EMBO Rep, 2016)
The election of Donald Trump highlights the need for all scientists to actively engage in communicating with the public to fight a post‐truth environment that could have dire consequences for science. [Image: see text]